Ubiquitin-Specific Protease 2 Modulates the Lipopolysaccharide-Elicited Expression of Proinflammatory Cytokines in Macrophage-like HL-60 Cells - Kitamura, Hiroshi; Ishino, Takeshi; Shimamoto, Yoshinori; Okabe, Jun; Miyamoto, Tomomi; Takahashi, Eiki; Miyoshi, Ichiro (Mediators of Inflammation, 2017)
We investigated the regulatory roles of USP2 in mRNA accumulation of proinflammatory cytokines in macrophage-like cells after stimulation with a toll-like receptor (TLR) 4 ligand, lipopolysaccharide (LPS). Human macrophage-like HL-60 cells, mouse macrophage-like J774.1 cells, and mouse peritoneal macrophages demonstrated negative feedback to USP2 mRNA levels after LPS stimulation, suggesting that USP2 plays a significant role in LPS-stimulated macrophages. USP2 knockdown (KD) by short hairpin RNA in HL-60 cells promoted the accumulation of transcripts for 25 of 104 cytokines after LPS stimulation. In contrast, limited induction of cytokines was observed in cells forcibly expressing the longer splice variant of USP2 (USP2A), or in peritoneal macrophages isolated from Usp2a transgenic mice. An ubiquitin isopeptidase-deficient USP2A mutant failed to suppress LPS-induced cytokine expression, suggesting that protein ubiquitination contributes to USP2-mediated cytokine repression. Although USP2 deficiency did not accelerate TNF receptor-associated factor (TRAF) 6-nuclear factor-κB (NF-κB) signaling, it increased the DNA binding ratio of the octamer binding transcription factor (Oct)-1 to Oct-2 in TNF, CXCL8, CCL4, and IL6 promoters. USP2 decreased nuclear Oct-2 protein levels in addition to decreasing the polyubiquitination of Oct-1. In summary, USP2 modulates proinflammatory cytokine induction, possibly through modification of Oct proteins, in macrophages following TLR4 activation.